Management of congenital bladder diverticulum in children: A report of seven cases - Rachid Khemakhem; Sofiane Ghorbel; Said Jlidi; Faouzi Nouira; Héla Louati; Wiem Douira; Faouzia Chennoufi; Ibtisem Bellagha; Béji Chaouachi (Wolters Kluwer Medknow Publications, 2013)
Background: The purpose of the study is to present the author's experience with congenital bladder diverticula in seven pediatric patients at a developing world tertiary care center. Materials and Methods: Records of seven patients diagnosed and treated as congenital bladder diverticulum, from January 1998 to December 2009 were retrospectively reviewed for age, sex, clinical symptoms, investigative work-up, operative notes, and postoperative follow-up. Results: All patients were males. Age at presentation ranged from six months to six years (mean three years and six months). All were manifested postnatally by urinary tract infection in four cases, bladder retention in three cases and abdominal pain in two cases. Diagnosis was suggested by ultrasound and confirmed by voiding cystourethrography (VCUG) in all cases and urethrocystoscopy in three cases. Open surgical excision of diverticulum was done in all the patients associated with ureteral reimplantation in four patients with VCUG-documented high-grade vesicoureteral reflux (VUR). Average follow-up was four years; there is a resolution of symptoms and no diverticulum recurrence at the defined mean follow-up. Conclusion: Recurrent urinary tract infections and voiding dysfunction in pediatric population should always be evaluated for congenital bladder diverticulum. Investigations such as abdominal ultrasound, VCUG and nuclear renal scanning, form an important part of preoperative diagnostic work-up and postoperative follow up. Diverticulectomy with ureteral reimplantation in case of high-grade reflux, provides good results without recurrence.